CIRCULAR ECONOMY AND FOOD PRODUCTION SYSTEMS: TRACING LINKAGES AND EXPLORING SYNERGIES - Vasiliki A. GKOUNTANI; Giannis T. TSOULFAS (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Food production systems have been in the spotlight for a sustainable conversion due to their environmental, economic, and social impacts. On the other hand, the concept of circular economy has been promoted as a promising alternative for various production systems. By decomposing the agri-food supply chain to its core components, i.e. primary production, food processing and distribution, certain interventions may be assessed through the lens of circular economy. In this paper we focus on the stages of food processing and manufacturing in order to analyze how the application of circular economy perspectives in closing material loops contributes towards minimizing the economic and environmental impacts of food production systems, in opposition to the widely applied linear economy model. Moreover, we explore from a managerial perspective the new technological advancements for waste minimization and valorization and critically discuss the new business models that emerge, along with the redefined value chains.